2018
DOI: 10.1186/s12958-018-0373-7
|View full text |Cite
|
Sign up to set email alerts
|

Progestin-primed milder stimulation with clomiphene citrate yields fewer oocytes and suboptimal pregnancy outcomes compared with the standard progestin-primed ovarian stimulation in infertile women with polycystic ovarian syndrome

Abstract: BackgroundOral progestin has recently been used to prevent premature LH surges in ovarian stimulation, and this progestin-primed ovarian stimulation (PPOS) is effective and safe in patients with different ovarian reserves. The current data are lacking regarding how to individualize the gonadotropin dose and regimen for women with polycystic ovarian syndrome (PCOS). A retrospective cohort trial was performed to evaluate the efficacy of progestin-primed milder stimulation with clomiphene citrate (CC) compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…CC interacts with hypothalamic estrogen receptors and increases endogenous FSH and LH secretion by blocking the estrogen-negative feedback mechanism. 11 , 24 , 25 Our data are consistent with previous findings 5 , 6 and showed that LH levels on days 7–10 and the day of trigger in PPOS+CC were significantly higher than in all subgroups of standard PPOS ( P < 0.05). Furthermore, the E 2 levels and P levels on trigger day were significantly higher in PPOS+CC than in standard PPOS ( P < 0.01).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CC interacts with hypothalamic estrogen receptors and increases endogenous FSH and LH secretion by blocking the estrogen-negative feedback mechanism. 11 , 24 , 25 Our data are consistent with previous findings 5 , 6 and showed that LH levels on days 7–10 and the day of trigger in PPOS+CC were significantly higher than in all subgroups of standard PPOS ( P < 0.05). Furthermore, the E 2 levels and P levels on trigger day were significantly higher in PPOS+CC than in standard PPOS ( P < 0.01).…”
Section: Discussionsupporting
confidence: 92%
“… 11 , 12 PPOS supplemented with CC (PPOS+CC) significantly reduces the occurrence of profound pituitary suppression in women with normal ovarian reserve or polycystic ovarian syndrome, and the combination treatment is likely to reduce Gn consumption compared with PPOS treatment alone. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…In these regimens both GnRH antagonists and endogenous progesterone exerted suppressive influence and consequently resulted in much more profound pituitary suppression and therefore much higher dosage of FSH or longer stimulation duration. Long-acting FSH has also been used in a fashion of random start with antagonist protocol [26], but there is lack of investigation specific to luteal stimulation. As for PPOS without GnRH antagonist, the group in China led by Kuang [8,10,27 Almost all previous relevant studies unanimously required higher dosage of HMG with or without longer duration for stimulation in MPA-PPOS [8,12,33].…”
Section: Resultsmentioning
confidence: 99%
“…The difference might emerge in low responders stimulated with only FSH instead of HMG or FSH + LH. On the other hand, it seems that clomiphene co-administration is able to avoid LH oversuppression in PPOS, which resulted in an initial slight rise followed by a downward trend in LH, although the limited data came from normal responders [33] and high responders [34]. If we consider extending our long-acting FSH PPOS application to low responders, different progestin and clomiphene combinations might be necessary in PPOS with long-acting FSH where no exogenous LH is given in the first week.…”
Section: Discussionmentioning
confidence: 99%